Emerging Bio‐Interfacing Wearable Devices for Signal Monitoring: Overview of the Mechanisms and Diverse Sensor Designs to Target Distinct Physiological Bio‐Parameters. Issue 4 (15th January 2023) - Kim, Moohyun; Kim, Sumin; Kwon, Yong Won; Seo, Hunkyu; Chung, Won Gi; Kim, Enji; Park, Wonjung; Song, Hayoung; Lee, Dong Ha; Lee, Jakyoung; Lee, Sanghoon; Jeong, Inhea; et al.
Abstract: Recently, personalized medical diagnostics and treatments have received significant interest due to the rising demand for reliable, rapid, and cost‐effective healthcare services. In the recent development of wearable devices, ways to engineer devices to extend their reliability, minimize the risk of infection, and expand the scope of application have been focused on improving conventional clinical procedures. With the increasing interest in personalized healthcare, wearable devices have received substantial interest because they monitor each physiological parameter for specific clinical interest. These unique bio‐parameters of individuals can be recorded from different target organs for the analysis of various functions, ranging from simple bodily movement to clinical treatment. In this review, the recent advances in sensors for recording unique bio‐signals from the human body are discussed. Based on each unique bio‐signals, a comprehensive analysis of wearable platforms for clinical diagnosis is provided, including subjects such as the selection of materials, device design structure, and application strategies for therapeutic significance. Furthermore, the challenges and future potential direction of modern bio‐sensor devices are discussed extensively. Abstract : Recent advances and development in wearable diagnostic devices are discussed. For the precise evaluation of different biosignals of the human body, the choice of sensor material and device design must be optimized for the dynamic nature of the body. Various engineering methods to characterize these biosignals signals are discussed in this review with perspectives on the future direction of various wearable platforms.